Optimization Formulas Tablet Extract of Bay Leaf (Eugenia polyantha Wight.) With the Binder PVP and Desintegrant Sodium Alginate Using Simplex Lattice Design Method - Safitri, Rizki Amalia; , Erindyah Retno Wikantyasning, Ph.D., Apt (2016)
Flavonoid in Eugenia polyantha Wight. can be used as analgesic. Previous study showed that the water extract of Eugenia polyantha Wight. at the dose of 25 mg/kg cause analgesic effect in mice. The purpose of this research was to determine the concentration of binder (PVP) and desintegrant tablet (sodium alginate) to obtain optimum formulae of Eugenia polyantha Wight. tablet. Tablets made eight formula use Simplex Lattice Design method with various concentration of PVP and sodium alginate. Optimization of formulas was conduated by Design Expert 10.0.2.0 (trial) program using the parameters of flow rate, angle of repose, tapped density, uniformity of weight, hardness, friability, and desintegration time. The optimum formulae was further verified and analyzed using SPSS 23. The optimum formulae was combination of PVP 2,62% and 5,37% sodium alginate. The results showed that using One-Sample T Test showed there is a significancy for flow rate, hardness, and desintegration time. Significancy was shown that value of p, there is not significant if value of p> 0,05, that is angle of repose, tapped density, uniformity of weight, and friability.